ICTERÍCIA, ANEMIA HEMOLÍTICA E KERNICTERUS NEONATAL APÓS TRATAMENTO COM NITROFURANTOÍNA EM GESTANTES DE TERCEIRO TRIMESTRE: UMA REVISÃO SISTEMÁTICA - JOSE HYDEMITSU HIGA (2024)
INTRODUCTION: Primary Health Care (PHC) is the gateway to the Unified Health System (SUS) and integrates the entire Health Care Network (RAS). Normal-risk prenatal care is conducted in primary care units. Urinary tract infections (UTI) occurs in up to 15% of pregnant women and is a important factor by PHC professionals. Early diagnosis and treatment of UTI are crucial due to the potential increased risk of complications such as labor, miscarriage, prematurity, low birth weight, premature rupture of membranes, maternal sepsis, anemia, preeclampsia, and other conditions that increase morbidity and mortality of the maternal-fetal binomial. Nitrofurantoin is the main treatment for UTI in the general population; however, it is contraindicated for treating pregnant women from the third trimester onwards due to a supposed increased risk of hemolytic anemia, kernicterus, and/or neonatal jaundice. However, this is not well established in the scientific literature. Due to a scarcity of clinical studies, most drug labels contain restrictions or even contraindications based on studies susceptible to biases, with small sample sizes and contradictory or inconclusive results. OBJECTIVE: To conduct a systematic review to assess the risk of hemolytic anemia, kernicterus, and jaundice in neonates whose mothers were treated with nitrofurantoin in the third trimester of pregnancy. RESULTS: The systematic review protocol was registered in PROSPERO Database of Systematic Review Protocols and can be identified by CRD42023418798. The systematic review includes a single cohort study with moderate overall risk of bias. Very low-quality evidence according to the GRADE system indicates that nitrofurantoin had no significant difference compared to the antibiotic pivmecillinam for the outcomes jaundice, hemolytic anemia, and neonatal kernicterus. The comparison between nitrofurantoin exposed group and not exposed to antibiotics group showed an increased chance of neonatal jaundice in the intervention group (OR 1.33; 95% CI 1.09–1.64; p = 0.006), and a non-significant difference for the outcomes of hemolytic anemia and kernicterus. CONCLUSION: The results presented in this review demonstrated that the available scientific evidence does not support an increased risk in the use of nitrofurantoin compared to other antibiotics; however, the quality of the evidence is still very low, and further studies are needed. RELEVANCE, IMPACT AND APPLICABILITY: Improving a response to this question can provide practitioners health working in the primary care with alternatives in the management of UTI and offer safer therapies for pregnant women. This is especially relevant when Nitrofurantoin is the only antibiotic to which the identified strain does not present resistance, or when it is the only option available in the network. Key-words: Hemolytic Anemia; Family Health Strategy; Nitrofurantoin; Kernicterus; Neonatal Jaundice